2017
DOI: 10.1007/s10784-017-9364-y
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic political contexts and power asymmetries: the cases of the Blue Nile and the Yarmouk Rivers

Abstract: This paper explores the evolving patterns of hydropolitical relations in the dynamic contexts of Yarmouk and Blue Nile Rivers in comparison. The analysis aims at shedding light over the complex implications that recent political and social changes have aroused for the water disputes between Jordan and Syria on the one hand, and Ethiopia and Egypt on the other. In both basins, cooperative efforts toward the integrated management of transboundary waters have been only partially effective and largely undermined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 39 publications
0
46
0
1
Order By: Relevance
“…An alternative to the mainstream discourse on water governance is the Framework on Hydro-Hegemony (FHH) introduced by Zeitoun and Warner [32] and developed to analyze trans-boundary water conflicts. It has been widely employed at a river basin level [33] and provides an understanding of how three forms of power ("hard" or structural power; covert or bargaining power to shape agendas; and "ideational" power to shape perceptions and discourses) are used [34] and the nature of power asymmetries. While the FHH is not a governance framework per se, it does provide an effective means to better understand socio-political-economic relations in relation to water, and how these relations determine water outcomes.…”
Section: Existing Water Governance Principles and Frameworkmentioning
confidence: 99%
“…An alternative to the mainstream discourse on water governance is the Framework on Hydro-Hegemony (FHH) introduced by Zeitoun and Warner [32] and developed to analyze trans-boundary water conflicts. It has been widely employed at a river basin level [33] and provides an understanding of how three forms of power ("hard" or structural power; covert or bargaining power to shape agendas; and "ideational" power to shape perceptions and discourses) are used [34] and the nature of power asymmetries. While the FHH is not a governance framework per se, it does provide an effective means to better understand socio-political-economic relations in relation to water, and how these relations determine water outcomes.…”
Section: Existing Water Governance Principles and Frameworkmentioning
confidence: 99%
“…Others looked at how the domestic political context has shaped transboundary water policies of riparian states (Menga 2015;Carkoglu and Eder 2001). Likewise, the recent study conducted by Hussein and Grandi (2017) looks at the relationship between power and broader political contexts. Building on these studies, this paper argues that the empirical evidence derived from hydropolitical interactions among Lebanon, Syria and Turkey suggests that the historical and political context strongly influences riparian states' transboundary water interactions on the Orontes Basin.…”
Section: General Overview Of the Orontes Basin Hydropolitics: Broadermentioning
confidence: 99%
“…SDG indicator 6.5.2 takes the first approach [37,40]. To strengthen SDG 6.5.2 various researchers propose either a cooperation continuum [41] or qualitative analyses, including hydropolitical assessments and discourse analyses [37,[42][43][44][45][46][47][48][49][50][51][52][53][54][55]. Based on relevant literature review, we identified ten Indicator 6.5.2 gaps, as discussed in this sub-section.…”
Section: Identified Policy Gaps: Sdg 652mentioning
confidence: 99%